Characteristics and treatment of congenital perineal groove in male patients - Wang, Kai; Pang, Wenbo; Chen, Wei; Zhang, Dan; Wu, Dongyang; Chen, Yajun (Frontiers in Pediatrics, 2023)
Background: Congenital perineal groove (CPG) of male patients has rarely been reported before. The purpose of this study was to review our cases and describe their characteristics and treatment. Methods: 4 male patients diagnosed with CPG were included in this study. Medical records were retrospectively reviewed. Type of CPG and anal position index (API) of the patients were recorded. Follow-up was through outpatient visits. Results: Their age ranged from 4 years and 2 months to 10 years and 9 months. Among the 4 patients, 2 complained of intermittent CPG mucosal hemorrhage, the other 2 had mucous secreting and soiling. The API was 0.24, 0.35, 0.36, 0.40 for each patient, all represented anterior displacement. Type of CPG for the 4 patients were all partial, and the sulcus was from the posterior perineum to the edge of anus. 2 patients were associated with hydrocele, imperforated anus and rectoperineal fistula; 1 patient had left varicocele; the remaining patient had sacrum split. All the patients had no postoperative complication, and during the follow-up period of 5 to 8 months, no symptoms recurred in the 4 patients, and they all had normal defecation. Conclusions: Both genders share the common 3 characteristics. Besides, shortened perineum with anterior anus, association of perineal malformations, and partial type occurrence are the extra morphological features in male patients. Furthermore, CPG in males are rarely accompanied by urinary tract infection. Favorable prognosis could be reached after operation.